Macrostomum lignano as a model to study the genetics and genomics of parasitic flatworms - K. V. Ustyantsev; V. Yu. Vavilova; A. G. Blinov; E. V. Berezikov (Вавиловский журнал генетики и селекции, 2021)
Hundreds of millions of people worldwide are infected by various species of parasitic flatworms. Without treatment, acute and chronical infections frequently lead to the development of severe pathologies and even death. Emerging data on a decreasing eff iciency of some important anthelmintic compounds and the emergence of resistance to them force the search for alternative drugs. Parasitic flatworms have complex life cycles, are laborious and expensive in culturing, and have a range of anatomic and physiological adaptations that complicate the application of standard molecular-biological methods. On the other hand, free-living flatworm species, evolutionarily close to parasitic flatworms, do not have the abovementioned diff iculties, which makes them potential alternative models to search for and study homologous genes. In this review, we describe the use of the basal free-living flatworm Macrostomum lignano as such a model. M. lignano has a number of convenient biological and experimental properties, such as fast reproduction, easy and non-expensive laboratory culturing, optical body transparency, obligatory sexual reproduction, annotated genome and transcriptome assemblies, and the availability of modern molecular methods, including transgenesis, gene knockdown by RNA interference, and in situ hybridization. All this makes M. lignano amenable to the most modern approaches of forward and reverse genetics, such as transposon insertional mutagenesis and methods of targeted genome editing by the CRISPR/Cas9 system. Due to the availability of an increasing number of genome and transcriptome assemblies of different parasitic flatworm species, new knowledge generated by studying M. lignano can be easily translated to parasitic f latworms with the help of modern bioinformatic methods of comparative genomics and transcriptomics. In support of this, we provide the results of our bioinformatics search and analysis of genes homologous between M. lignano and parasitic flatworms, which predicts a list of promising gene targets for subsequent research.